In vitro Micropropagation and Antioxidant Assay in Colocasia esculenta (Plant Tissue Culture and Biotechnology, 2018)
The present work was intended to establish an efficient and reproducible direct regeneration protocol in Colocasia esculenta and to compare the levels of total phenolics and free radical scavenging activity in in vitro regenerated and wild type plants. In vitro micropropogation protocol of the C. esculenta plant was optimized using meristem as explant. The surface sterilized explants were inoculated on MS supplemented with varied concentration and combination of auxin and cytokinins. The cultures were maintained at 26ºC under a 12 hrs photoperiod. Total phenolic content and free radical scavenging assay was carried out in wild type plants and compared with in vitro micropropagated plants using DPPH method. Statistical analysis of the data was carried out using STATISTICA 13 software. An efficient in vitro micropropagation protocol was established for C. esculenta. Antioxidant activity and total phenolic content was marginally increased in tissue cultured plants compared to wild type plants of C. esculenta.Plant Tissue Cult. & Biotech. 28(2): 183-190, 2018 (December)